Internato médico: construção de modelo de autoavaliação institucional e educacional - Farias Filho, Alberto (2018)
Nowadays, there is a great debate about the quality of medical education and a great number of instruments of evaluation, with several approaches and scope, that bring in a dispersed way criteria and dimensions that allow to establish the evaluation of undergraduate courses, nevertheless, do not seem to be focused on the specificities of the Internship.From a quadripolar strategy, epistemological, theoretical, technical and morphological poles, a model of institutional and educational self-assessment,of the Medical Internship,is constructed.At the epistemological pole,the phenomenotechnicof Gaston Bachelard exerts critical surveillance of the scientific knowledge regarding the object of evaluation and the self-evaluation ofthe Medical internship. In the theoretical pole, the structural-systemic frame of reference creates the bases for the elaboration of a model of self-evaluation institutional and educational of the Medical internship.Inthe technical pole,bibliographicalresearch,from educational evaluation models and from Curricular Guidelines, lay thefoundation to theconstruction of self-evaluation model of the Medical internship, in the morphological pole, from the analysis frame structural-systemic approach, based on the concept of essential macro-structures of Higher Education.